Prey perception mechanism determines maximum clearance rates of planktonic copepods. (24th July 2018) - Almeda, Rodrigo; van Someren Gréve, Hans; Kiørboe, Thomas
Abstract: The ecological consequences of "sit‐and‐wait" (ambushing) vs. "searching" (active feeding) foraging strategies are not well‐understood in marine plankton food webs. We determined the maximum clearance rates of ambush and active feeders to evaluate the trade‐off between foraging gain and predation risk associated with the main foraging strategies in planktonic copepods. We show that maximum clearance rates are similar among feeding behaviors for motile prey but one order of magnitude lower for ambush than for active feeders toward nonmotile prey. The prey size spectrum is narrower and toward relatively larger prey in ambushers compared with active feeders. Prey detection in ambushers relies on the hydrodynamic disturbances and is inefficient toward nonmotile prey but highly efficient for large motile prey. The effective prey perception mechanism in ambushers compensates for the lower prey encounter velocity in ambush feeding copepods compared with active feeding copepods. Therefore, ambushers are more restricted in target prey than active feeders and prey perception mechanism determines the efficiency of planktonic copepod foraging strategies. The lower clearance rates of ambush feeders on nonmotile prey is compensated for by a lower predation risk, which can partially explain the coexistence of both "high‐gain & high‐risk" (active feeders) and "low‐gain & low‐risk" (ambush feeders) foraging strategies in marine plankton food webs.